(De)Mystifying the information and communication technology business model concept. (28th June 2019) - Clohessy, Trevor; Acton, Thomas; Morgan, Lorraine
Modern enterprises are currently experiencing volatile and rapid information and communication technology (ICT) change. A key challenge for business leaders is to ensure their organisations are ready for that change. This is particularly challenging when it comes to emerging ICT that may disrupt the management of existing enterprise information systems or business processes. The business model has been cited as an effective tool which organisations can use to prepare for ICT related change. However, there is evidence to suggest that the business model remains largely a nebulous concept to most organisations. This is compounded by the siloed nature of existing business model research. Using a content analysis research approach, this paper provides a holistic review of contemporary academic literature to ascertain and classify the various approaches to the study of ICT enabled business models. The literature examined is classified into nine specific thematic descriptors which underpin these specific business models. A comprehensive definition is also developed for ICT business models. This paper therefore extends our understanding of the business model concept and can be used to guide and coalesce future research on illuminating how organisations can operationalise effective business models in order to leverage new digital ICT.